2000
DOI: 10.1046/j.1464-410x.2000.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, controlled, randomized study of the effect of a slow‐release silver device on the frequency of urinary tract infection in newly catheterized patients

Abstract: Objective To test the effect on urinary tract infections (UTIs) in patients needing continuous indwelling catheterization, of a newly designed urine-collecting system containing an antibacterial device which slowly releases silver ions onto the inner surface of the system. Patients and methods The study comprised a prospective controlled randomized trial; 213 patients ful®lled the inclusion criteria. They were randomized to a urine drainage system (comprising a Unometer 400 metering system or PP 2000N closed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 23 publications
0
16
0
1
Order By: Relevance
“…Randomized trials of the addition of antimicrobials (including chlorhexidine, hydrogen peroxide, povidone-iodine, or slowly released silver ions) to the drainage bag to decrease the risk of CA-bacteriuria have generally shown no benefit [29,150,[272][273][274]. For example, in 668 patients with indwelling urethral catheters (mean duration, 4 days), there was no difference between the hydrogen peroxide group and the control group with respect to the mean duration of catheterization before the onset of bacteriuria, the rate of CA-bacteriuria, or the spectrum of etiologic agents recovered [150].…”
Section: Evidence Summarymentioning
confidence: 99%
“…Randomized trials of the addition of antimicrobials (including chlorhexidine, hydrogen peroxide, povidone-iodine, or slowly released silver ions) to the drainage bag to decrease the risk of CA-bacteriuria have generally shown no benefit [29,150,[272][273][274]. For example, in 668 patients with indwelling urethral catheters (mean duration, 4 days), there was no difference between the hydrogen peroxide group and the control group with respect to the mean duration of catheterization before the onset of bacteriuria, the rate of CA-bacteriuria, or the spectrum of etiologic agents recovered [150].…”
Section: Evidence Summarymentioning
confidence: 99%
“…In comparison to organic antibiotic, silver ions are active against a broad spectrum of bacteria, viruses, and fungi, and the risk of resistance development is much lower. For these reasons, medical devices like catheters (18)(19)(20)(21)(22)(23)(24)(25), heart valve sewing cuffs (21,26,27), wound dressings (2,(28)(29)(30)(31)(32)(33), or sutures (21,34) are coated with elemental silver (2,21,26,27,30,31,33), silver sulfadiazine (18, 19, 21-23, 28-30, 33), silver ion containing hydrogels (21,25,33), or silver ion doped bioglasses (20,24,34) to minimize the risk of infection. The antimicrobial efficacy of coatings containing ionic silver or elemental silver nanoparticles was shown in many studies.…”
Section: Introductionmentioning
confidence: 99%
“…These studies found no clear benefit from using either preconnected sealed systems, or from the use of sealed systems with the addition of silver releasing devices. [28][29][30][31]33 One study found in favour of hydrophilic-coated silicone catheters, but the sample size was small, although these findings do suggest further research is warranted. 32…”
Section: Discussionmentioning
confidence: 99%
“…30 Subjects aged ≥18 and requiring continuous catheterisation were recruited from all medical and surgical specialties from a tertiary facility in Copenhagen. Exclusion criteria included existing UTI, onset of UTI within 48 h of recruitment to the study, and the presence of any concentration of microbes in their urine on day 1 of the study.…”
Section: Closed Drainage With a Silver Releasing Devicementioning
confidence: 99%